Stephens' C# Programming with Visual Studio® 2010 24-Hour Trainer - Stephens, Rod (Wrox, 2010)
A unique book-and-video package for Stephens' C# Programming with Visual Studio® 2010 24-Hour Trainer Visual C# has become a leading programming language, resulting in greater career opportunities for Visual C# programmers. This Wrox guide literally shows novice programmers how to program in C# with Microsoft Visual Studio, using both written and visual instruction. Easy-to-follow lessons reinforced with step-by-step instructions, screencasts, and supplemental exercises make it easy to master Visual C# programming regardless of your learning style. Each lesson begins with a discussion of a concept or technique and proceeds through step-by-step directions for using the technique Visual C# has surpassed Visual Basic as the most popular programming language.